Capital Structure and Financial Distress: Empirical Study of Companies in the Mining Sector and the Infrastructure, Utilities & Transportation Sector - Devi Wahyu Utami; Heni Hirawati; Axel Giovanni (Kusuma Negara Business School, 2020)
This study aims to provide empirical evidence about the effect of capital structure on financial distress in mining sector companies and the infrastructure, utilities and transportation sectors for the 2014-2018 period. The research sample was 37 companies in the mining sector and 44 companies in the infrastructure, utility and transportation sectors which were obtained through purposive sampling method. The data analysis technique uses logistic regression. The results provide evidence of a negative and significant relationship between capital structure and financial distress in the mining sector as well as a positive and significant relationship between capital structure and financial distress in the infrastructure, utility and transportation sectors.